Pancreatobiliary manifestations of nonalcoholic fatty liver disease: a retrospective case-control multicenter study. Issue 5 (May 2021) - Sbeit, Wisam; Greener, Tomer; Kadah, Anas; Mari, Amir; Goldin, Eran; Khoury, Tawfik; Mahamid, Mahmud
Abstract : Background: Nonalcoholic fatty liver disease (NAFLD) has become a major cause of chronic liver disease. Several extrahepatic manifestations have been reported in relation to NAFLD. However, data regarding pancreatobiliary manifestation are scarce. Aim: We aimed to explore the association of pancreatobiliary manifestation with NAFLD. Methods: A retrospective multicenter study that included all patients who underwent an endoscopic ultrasound performed for hepatobiliary indications and for whom the endosonographer reported on the presence or absence of fatty liver. The endoscopic ultrasound reports were reviewed and all pathological findings were reported. Results: Overall, 545 patients were included in the study, among them, 278 patients had fatty liver (group A) as compared to 267 who did not have (group B). The average age in group A was 64.5 ± 13.5 years vs. 61.2 ± 14.7 years in group B. Male sex constituted 49.6 and 58% in groups A and B, respectively. On multivariate analysis, fatty pancreas [odds ratio (OR) 4.02; P  = 0.001], serous cystadenoma (SCA) (OR 5.1; P  = 0.0009), mucinous cystadenoma (MCA) (OR 9.7; P  = 0.005), side-branch intraductal papillary mucinous neoplasm (IPMN) (OR 2.76; P  < 0.0001), mixed-type IPMN (OR 16.4; P  = 0.0004), pancreatic neuroendocrine tumor (NET) (OR 8.76; P  < 0.0001), gallbladder stones (OR 1.9; P  = 0.02) and hilar lymphadenopathy (OR 6.8; P  < 0.0001) were significantly higher among patients with NAFLD. After adjustment for fatty pancreas, the association remained significant for SCA (OR 3; P  = 0.01), MCA (OR 4.6; P  = 0.03), side-branch IPMN (OR 1.7; P  = 0.02), mixed-type IPMN (OR 5.5; P  = 0.01) and pancreatic NET (OR 4.5; P  = 0.001). Conclusion: Pancreatobiliary manifestations are common among patients with NAFLD. Assessment of these coexistent manifestations should be considered in the setting of patients with NAFLD.